High Cysteine Membrane Proteins (HCMPs) Are Up-Regulated During Giardia-Host Cell Interactions - Peirasmaki, Dimitra; Ma’ayeh, Showgy Y.; Xu, Feifei; Ferella, Marcela; Campos, Sara; Liu, Jingyi; Svärd, Staffan G. (Frontiers in Genetics, 2020)
Giardia intestinalis colonizes the upper small intestine of humans and animals, causing the diarrheal disease giardiasis. This unicellular eukaryotic parasite is not invasive but it attaches to the surface of small intestinal epithelial cells (IECs), disrupting the epithelial barrier. Here, we used an in vitro model of the parasite’s interaction with host IECs (differentiated Caco-2 cells) and RNA sequencing (RNAseq) to identify differentially expressed genes (DEGs) in Giardia, which might relate to the establishment of infection and disease induction. Giardia trophozoites interacted with differentiated Caco-2 cells for 1.5, 3 and 4.5hrs and at each time point, 61, 89 and 148 parasite genes were up-regulated more than 2-fold, whereas 209, 265 and 313 parasite genes were down-regulated more than 2-fold. The most abundant DEGs encode hypothetical proteins and members of the High Cysteine Membrane Protein (HCMP) family. Among the up-regulated genes we also observed proteins associated with proteolysis, cellular redox balance, as well as lipid and nucleic acid metabolic pathways. In contrast, genes encoding kinases, regulators of the cell cycle and arginine metabolism and cytoskeletal proteins were down-regulated. Immunofluorescence imaging of selected, up-regulated HCMPs, using C-terminal HA-tagging, showed localization to the plasma membrane and peripheral vesicles (PVs). The expression of the HCMPs was affected by histone acetylation and free iron-levels. In fact, the latter was shown to regulate the expression of many putative giardial virulence factors in subsequent RNAseq experiments. We suggest that the plasma membrane localized and differentially expressed HCMPs play important roles during Giardia-host cell interactions.